CHIP‐associated mutant ASXL1 in blood cells promotes solid tumor progression. Issue 4 (26th February 2022) - Liu, Xiaoxiao; Sato, Naru; Shimosato, Yuko; Wang, Teh‐Wei; Denda, Tamami; Chang, Yu‐Hsuan; Yabushita, Tomohiro; Fujino, Takeshi; Asada, Shuhei; Tanaka, Yosuke; Fukuyama, Tomofusa; Enomoto, Yutaka; et al.
Abstract: Clonal hematopoiesis of indeterminate potential (CHIP) is an age‐associated phenomenon characterized by clonal expansion of blood cells harboring somatic mutations in hematopoietic genes, including DNMT3A, TET2, and ASXL1 . Clinical evidence suggests that CHIP is highly prevalent and associated with poor prognosis in solid‐tumor patients. However, whether blood cells with CHIP mutations play a causal role in promoting the development of solid tumors remained unclear. Using conditional knock‐in mice that express CHIP‐associated mutant Asxl1 (Asxl1‐MT), we showed that expression of Asxl1‐MT in T cells, but not in myeloid cells, promoted solid‐tumor progression in syngeneic transplantation models. We also demonstrated that Asxl1‐MT–expressing blood cells accelerated the development of spontaneous mammary tumors induced by MMTV‐PyMT. Intratumor analysis of the mammary tumors revealed the reduced T‐cell infiltration at tumor sites and programmed death receptor‐1 (PD‐1) upregulation in CD8 + T cells in MMTV‐PyMT/Asxl1‐MT mice. In addition, we found that Asxl1‐MT induced T‐cell dysregulation, including aberrant intrathymic T‐cell development, decreased CD4/CD8 ratio, and naïve‐memory imbalance in peripheral T cells. These results indicate that Asxl1‐MT perturbs T‐cell development and function, which contributes to creating a protumor microenvironment for solid tumors. Thus, our findings raise the possibility that ASXL1 ‐mutated blood cells exacerbate solid‐tumor progression in ASXL1‐CHIP carriers. Abstract : ASXL1 mutations found in CHIP carriers alter T‐cell development and function, which contributes to creating a protumor environment for solid tumors.